Modelling Category Inflation with Multiple Inflation Processes: Estimation, Specification and Testing - Brown, S.; Harris, Mark; Spencer, C. (WILEY, 2020)
© 2020 The Department of Economics, University of Oxford and John Wiley & Sons Ltd